The effect of social media marketing and religiosity on perceived value and student’s decision in choosing non-religious program at Islamic higher education - Lutfi Auliarahman; Sumadi Sumadi (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This study aims to examine the effect of social media marketing and religiosity on perceived value and student’s decision in choosing non-religious programs at Islamic Higher Education.Methodology: This study conducted an online survey on 158 respondents who are studying non-religious programs in three Islamic Higher Education institutions in Indonesia, namely Universitas Islam Indonesia, Universitas Muhammadiyah Yogyakarta, and Universitas Islam Negeri Sunan Kalijaga. The data was analysed using Partial Least Square Structural Equation Modeling (PLS-SEM).Findings: The results show that social media marketing and religiosity have a positive and significant impact on perceived value. Social media marketing has a positive but insignificant impact on student’s decision and religiosity has a negative but insignificant impact on student’s decision. Lastly, perceived value have a positive and significant impact on student’s decision.Originality: The need for higher education is increasing along with the demands of the working world which requires skills and professional abilities in accordance with the needs of the organization. This causes the interest of people to continue their studies to the higher education level is also increasing. Even so, the fierce competition between higher education institutions to get potential candidates in student enrollment forces them to struggle to survive, especially for Islamic Higher Education. Thus, it is important for hihger education institutions to implement effective marketing strategies.